Salmoneus yoyo nov. sp., a peculiar new infaunal shrimp from Lombok, Indonesia (Decapoda, Caridea, Alpheidae) - Anker, Arthur; Firdaus, Muhammad; Pratama, Idham Sumarto (Zootaxa, 2014)
An unusual new species of the alpheid shrimp genus Salmoneus Holthuis, 1955 is described from Sekotong Bay, southwestern Lombok, Indonesia. The holotype and single known specimen of Salmoneus yoyo sp. nov. was collected with a suction pump from a burrow of unknown host, on a seagrass flat partly exposed at low tide. The new species presents three characters on the chelipeds that are unique within Salmoneus: a conspicuous, mesially curved, hook-like process on the distomesial margin of the merus, a row of blunt teeth on the ventromesial margin of the merus, and a series of blunt teeth on the ventromesial margin of the propodus. Salmoneus yoyo sp. nov. also has a characteristic colour pattern consisting of bright red chromatophores occupying most of the carapace surface, except for the frontal and post-frontal areas.